2022
DOI: 10.35784/pe.2022.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Tax Policy for Economic Recovery and Sustainable Development After COVID-19

Abstract: The optimal taxation level and tax structure depend on numerous factors and enormously differ from country to country. However, the two mentioned tax policy instruments could ensure economic recovery and sustainable economic growth. This article aims to examine the effects of tax policy on economic development and evaluate the role of appropriate tax instruments in speeding up recovery. The results showed that tax level harms the GDP per capita growth rate in Central Europe and Baltic states over the 2000-2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Certainly, the ideal tax rate and tax system depend on a variety of variables and vary greatly from nation to nation. In a similar vein, Kaneva et al (2022) investigated how tax policy affected economic growth and assessed the contribution of relevant tax tools to accelerating several sector recoveries. The findings indicated that, between 2000 and 2021, tax levels in Central Europe and the Baltic States negatively impacted GDP per capita growth rates.…”
Section: Taxation and Economic Performancementioning
confidence: 99%
“…Certainly, the ideal tax rate and tax system depend on a variety of variables and vary greatly from nation to nation. In a similar vein, Kaneva et al (2022) investigated how tax policy affected economic growth and assessed the contribution of relevant tax tools to accelerating several sector recoveries. The findings indicated that, between 2000 and 2021, tax levels in Central Europe and the Baltic States negatively impacted GDP per capita growth rates.…”
Section: Taxation and Economic Performancementioning
confidence: 99%
“…For additional studies dealing with fiscal, social and environmental issues see for example Baye (2021), Samour et al (2022), Kouam andAsongu (2022), Vaquero García et al (2020), Dzingirai and Tambudzai (2014), Adeosun and Adebowale (2022), Kwilinski et al (2019), Trenta (2020), Munitlak Ivanović and Golušin (2012, Kalendienė and Pukelienė (2011), Tyuleneva and Moldazhanov (2020), Andrei et al (2016), Moosavian et al (2022), Wang (2022), Mcgill (2010), Kalkuhl et al (2017), Halim and Rahman (2022), Yang et al (2020), Xiao and Liu (2023), Ahmad et al (2023), López and Figueroa (2016), Kaneva et al (2022), O'Hare et al (2022, Liu et al (2023), Mosquera Valderrama (2020, Wang et al (2023).…”
Section: Introductionmentioning
confidence: 99%